SP4.2.11 Access to emergency theatre during the COVID -19 pandemic. (28th October 2021) - Dosis, Alexios; Lim, Jie Qi; Reveendran, Dharsshini; Paramjothy, Kiara; Lockwood, Sonia
Abstract: Aims: To investigate the impact of the COVID‐19 pandemic on general surgical emergencies and access to theatre during the pandemic. Methods: We retrospectively reviewed emergency theatre lists in three distinct time periods: October 2019 (pre-COVID-19 era), April 2020 (first peak) and October 2020 (regional second peak). We extracted and compared data from a prospectively maintained database to calculate patient waiting times. Statistical analysis was performed with SPSS software v21.0 to compare median waiting times between groups and significance was set to a p value of < 0.05. Results: Conclusions: Despite the initial major drop in general surgical procedures and waiting times, the decreased availability of theatre lists due to staff redeployment and sickness, the introduction of routine pre-operative COVID-19 testing have all resulted in a significant increase in waiting time for urgent (CEPOD 2A) cases during the second peak.